Risk factors for thrombosis risk in patients with cancer - Dilara Turan; Hatime Arzu Yasar; Ozge Bas Aksu; Elif Berna Koksoy; Gungor Utkan; Hakan Akbulut; Yuksel Urun (Journal of Oncological Sciences, 2018)
Aim: To evaluate the factors associated with Deep vein thrombosis (DVT) and pulmonary thromboembolism (PTE) in cancer patients. Materials and Methods: A total of 237 cancer patients who underwent lower extremity venous Doppler Ultrasonography (USG) and/or pulmonary computed tomography angiography (PCTA) were included. Patients’ demographic characteristics; chemotherapy data; immobilization status; use of central venous catheter; histories of 4-day-long bed rest, surgery within the last 6 months, long anesthesia for at least 2 hours, smoking, patients’ laboratory tests, ABO blood group, PCTA and lower extremity Doppler USG results were retrospectively reviewed through the hospital information management system. Results: The median age was 62 (age range 25 to 89). Thrombosis was detected in 83 patients according to the results of venous Doppler USG and/or PCTA of those patients who underwent imaging. Immobilization status (p=0.019), history of surgery within the last 6 months (p=0.02), anesthesia more than 2 hours (p=0.012) and 4-day-long bed rest (p=0.03) were found to be significantly associated with related risk of thrombosis. Additionally, thrombosis was found more frequently in the non-O group (especially group B) than in O group (p:0.024). Conclusions: Besides well-known risk factors, blood group may be related with risk of thrombosis in the patients with the cancer diagnosis Keywords: ABO blood group, Cancer, Pulmonary thromboembolism, Deep vein thrombosis